Insights into the wettability alteration of CO2-assisted EOR in carbonate reservoirs - Chen, Y.; Sari, A.; Xie, Q.; Saeedi, Ali (Elsevier, 2019)
Wettability of oil-brine-carbonate system is an important petro-physical parameter, which governs subsurface multiphase flow and residual oil saturation. CO2-assisted EOR techniques have been identified as cost-effective and environmentally friendly means to unlock remaining hydrocarbon resources from carbonate reservoirs. While wettability alteration appears to be one of the main mechanisms during CO2-assisted EOR implementation, the controlling factor(s) of wettability alteration at molecular level remains unclear. We thus hypothesized that excess of H+ as a result of water uptake of CO2 increases hydrophilicity of oil-brine-carbonate systems. More specifically, the surface charge properties will be alterated to more positive due to the increase of H+ in the brine. To test this hypothesis, we measured oil contact angles on calcite surfaces in the presence of non-carbonated brine, carbonated brine, and acidic brine (pH = 3). We also performed surface complexation modelling to examine how the surface chemistry controls over wettability of oil/brine/carbonate system using PHREEQC. Our contact angle results show that both carbonated brine and acidic brine gave a contact angle of 24° and 22° respectively, while non-carbonated brine gives a contact angle of 73° in 1 mol/L CaCl2 brines. Same trend was also observed in synthesized formation brine, showing that non-carbonated formation brine yielded a contact angle of 69° while both acidic formation brine and carbonated formation brine gave a contact angle of 37°. Experimental results show that both carbonated brine, and acidic brine significantly decreased contact angle compared to non-carbonated brine, suggesting a strong water-wet system. Surface complexation modelling shows that for both carbonated water and acidic water, >CaOH2+ dominates surface charges at calcite surfaces, and –NH+ governs surface charges on oil surfaces. Together, these two processes increase repulsive forces thus hydrophilicity. Our study sheds light on the significant influence of excess H+ due to water uptake of CO2 on oil-brine-carbonate system wettability thus enhancing hydrocarbon recovery in carbonate reservoirs.